Anterior Crowns in Pediatric Dentistry: A Review - Shrestha, Sneha; Koirala, Bandana; Dali, Mamta; Birajee, Gajendra (Journal of Nepalese Association of Pediatric Dentistry, 2020)
Anterior crowns have undoubtedly become one of the best discoveries in the field of pediatric dentistry today. There is a wide variation in the parental demand, availability and usage of pediatric anterior crowns worldwide. With the availability of a variety of anterior crowns in the market for children, the choice of selection is a question at hand for all the pediatric dentists. Continued update about these crowns will enhance our understanding about the topic and facilitate promotion of good clinical practice. Hence this review intends to highlight on all the anterior pediatric crowns available along with their recent advances. Evidence was collected via systematic searches through electronic databases, Pubmed and Google scholar.